The Influence of Storynomics and Tourism Products on Interest in Visiting Prambanan Temple Tourism Park Yogyakarta - Reiya Callista Sasi Kirana; Dewi Rahma Gian Salsabila; Estikowati; Anisa Zuhria Sugeha; Bambang Supriadi (Jurnal Penelitian, 2025)
This study aims to analyze the influence of storynomics and tourism products on interest in visiting Prambanan Temple Tourism Park, Yogyakarta. In an increasingly competitive era of globalization, the tourism sector must innovate in marketing strategies, especially after the impact of the COVID-19 pandemic. Storynomics that utilize local narratives and culture are expected to increase tourist interest. The research method used is quantitative with data collection through questionnaires from 100 respondents who have an interest in visiting. The results of the regression analysis show that storynomics and tourism products have a positive and significant influence on interest in visiting. The F test shows that both variables simultaneously have a significant influence. From the regression results, storynomics is proven to be the most dominant variable influencing interest in visiting. The emphasis on the story of Roro Jonggrang and tourism products such as local crafts and adequate facilities are the main attractions. This study underlines the importance of implementing a storynomics strategy in tourism promotion, as well as developing tourism products that can increase the attractiveness of Prambanan Temple Tourism Park. Thus, the combination of strong narratives and attractive products can create a unique experience for tourists. The results of this study are expected to contribute to destination managers in designing effective marketing strategies to increase tourist visits.